Characterization of Gibberellin Biosynthetic Gene Cluster from Fusarium proliferatum - Rim, S.O., Kyungpook National University, Daegu, Republic of Korea; You, Y.H., Kyungpook National University, Daegu, Republic of Korea; Yoon, H.J., Kyungpook National University, Daegu, Republic of Korea; Kim, Y.E., Kyungpook National University, Daegu, Republic of Korea; Lee, J.H., Kyungpook National University, Daegu, Republic of Korea; Kang, M.S., National Institute of Biological Resource, Incheon, Republic of Korea; Kim, C.M., National Institute of Biological Resource, Incheon, Republic of Korea; Seu, Y.B., Kyungpook National University, Daegu, Republic of Korea; Kim, J.G., Kyungpook National University, Daegu, Republic of Korea (Journal of microbiology and biotechnology, 2013)
Gibberellins (GAs) are a group of phytohormones that control many developmental processes in higher plants. We report the cloning and expression pattern of gibberellin biosynthesis genes from a new GA-producing fungus, Fusarium proliferatum (strain KGL0401). These genes sequences are deposited in the National Center for Biotechnology Information (NCBI) under accession numbers EF119831, EF119832, DQ313173, DQ313174, DQ313175, DQ313176, and DQ313177. The expression level of these genes was maximal at a 0.5 M : 0.17 M carbon : nitrogen ratio, and minimal at a 0.25 M : 0.47 M carbon : nitrogen ratio.